Motif Invasi Militer Rusia terhadap Ukraina Tahun 2022 - Ramadhan, Muhammad Fauzan Rizki (Jurnal Review Politik, 2023)
This research analyses the motives behind Russia's military invasion of Ukraine's sovereign territory in 2022. The invasion is a continuation of Russia's invasion of Crimea in 2014, and is part of a long history of conflict in the Eastern European region. This qualitative research focuses on Russia's perspective and how the country sees the main reasons for the conflict, namely the formation of 'the near abroad' policy and its link to the expansion of the US-led NATO (North Atlantic Treaty Organization) alliance. Using the theory of structural realism, this study tries to provide preliminary assumptions of motives with the conditions of international structures and their impact on Russia. This assumption is then strengthened by the elaboration of opinions from related research subjects, which can confirm these assumptions.